Convergence of modified homotopy perturbation method for Fredholm-Volterra integro-differential equation of order m - Eshkuvatov, Zainidin K.; Zulkarnain, Fatimah Samihah; Muminov, Zahriddin; Nik Long, Nik Mohd Asri (Penerbit UTM Press, 2017)
In this paper, modified homotopy perturbation method (MHPM) is applied to solve the general Fredholm-Volterra integro-differential equations (FV-IDEs) of order with initial conditions. Selective functions and unknown parameters allowed us to obtain two step iterations. It is found that MHPM is a semi-analytical method for FV-IDEs and could avoid complex computations. Numerical examples are given to show the efficiency and reliability of the method. Proof of the convergence of the proposed method is also given.